1979
DOI: 10.1002/anie.197907211
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dipolar Cycloreversions

Abstract: The 1,3-dipolar cycloreversion reaction represents a general scheme of fragmentation of pentaatomic heterocycles to produce 1,3-dipolar systems and dipolarophiles. This review summarizes cycloreversions which give rise to octet-stabilized 1,3-dipoles. The reaction can be either thermal or photochemical or electron impact induced. The aim of the article is to survey the published results, to emphasize the synthetic potential of this reaction, and to stimulate the study of its several not yet unambiguously defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 228 publications
0
12
0
Order By: Relevance
“…Crucially, though few in number, examples also exist of the retrocycloaddition of pyrazolidines. [45][46][47] For example, it was shown that cycloreversion of the ketone 137 could be accomplished by heating in xylenes over extended periods of time (Scheme 29a). 46b The resulting azomethine imine 138 was trapped by cycloaddition with norbornene (48) to furnish adduct 140 in 52% yield.…”
Section: Scheme 28 Selected Examples Of 13-dipolar Cycloadditions Of Azomethine Imines/hydrazonium Ionsmentioning
confidence: 99%
“…Crucially, though few in number, examples also exist of the retrocycloaddition of pyrazolidines. [45][46][47] For example, it was shown that cycloreversion of the ketone 137 could be accomplished by heating in xylenes over extended periods of time (Scheme 29a). 46b The resulting azomethine imine 138 was trapped by cycloaddition with norbornene (48) to furnish adduct 140 in 52% yield.…”
Section: Scheme 28 Selected Examples Of 13-dipolar Cycloadditions Of Azomethine Imines/hydrazonium Ionsmentioning
confidence: 99%
“…whereas oxazolidone/iminium equilibria were proposed during mechanistic studies of proline‐mediated aldol condensation reactions . Decarboxylation of thermally labile oxazolidin‐5‐one derivative ( IV′a ) furnishes azomethine ylides ( Va and Vb ) in a dipolar [3+2] cycloreversion step, as also discussed in literature for various oxazolidinone derivatives . As a final step, the azomethine ylides would undergo protonation and subsequent reduction by means of the metal hydride generated during the first dehydrogenation step, leading to the formation of the N ‐alkylated cyclic amine product ( VI ).…”
Section: Resultsmentioning
confidence: 89%
“…1d). On the other hand, relatively little work has been done regarding [3 + 2]cycloreversions generally, 32 or azomethine imine cycloreversions specically, 33,34 and so it was not clear to what extent such an undertaking would be successful. Nevertheless, we felt that gaining a deeper understanding of the catalyst and condition parameters that control the efficiency of hydrazine-catalyzed COM held great promise to make advancements in this area.…”
Section: Introductionmentioning
confidence: 99%